Three Familial Cases with Ectrodactyly Ectodermal Displazia-Clefting Syndrome - Dertlioglu, Selma Bakar; Cicek, Demet; Ozardali, Ilyas (Deri Zuhrevi Hastaliklar Dernegi, 2012)
A family of four children where mother and father had history of consanguineous marriage presented at our clinic due to lack of hair growth, thinning of all body hair and finger deformities in their three daughters aged 10 years, six years and three months. Dermatological examination of the cases showed thinning of the hair on the scalp, eyebrows, and extremities, subungual hyperkeratosis in nails, palmoplantar hyperkeratosis, cutaneous xerosis and loss of sweating, conical appearance and hypodontia in the teeth. All three siblings were seen to have the 3rd and 4th digits on the hand and the 2nd, 3rd and 4th digits on the feet to be proximally conjoined. Histopathologic examination of the cutaneous biopsy materials taken from the patients revealed a decrease in the number and size of hair follicles and sebaceous glands. We present these familial cases who were diagnosed with Ectrodactyly-ectodermal dysplasia-clefting syndrome as a result of clinical and histopathologic evaluation due to their rarity. (Turkderm 2012; 46: 47-9)
Ektrodaktili ektodermal displazi-klefting sendromlu ailesel üç olgu
Keywords: Ectrodactyly-ectodermal dysplasia-clefting syndrome; Ectodermal dysplasia-cutaneous syndactyly syndrome; ectodermal dysplasia